2017
DOI: 10.1007/s11605-016-3284-y
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy Reduces Recurrent Pancreatitis and Improves Survival After Endoscopic Sphincterotomy

Abstract: Cholecystectomy decreased the subsequent recurrent acute pancreatitis and the all-cause mortality in elderly patients with EST and clearance of BD stones after gallstone-related acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Taken together, the results of previous retrospective and prospective studies showed equivocal outcomes of recommendations for cholecystectomy [1][2][3][4][5][6][7][8][9][10][11]43]. However, several large-scale population-based studies and meta-analyses recommend cholecystectomy [28,31,32,36,37].…”
Section: Decision Of Prophylactic Cholecystectomy In the Real Worldmentioning
confidence: 95%
See 1 more Smart Citation
“…Taken together, the results of previous retrospective and prospective studies showed equivocal outcomes of recommendations for cholecystectomy [1][2][3][4][5][6][7][8][9][10][11]43]. However, several large-scale population-based studies and meta-analyses recommend cholecystectomy [28,31,32,36,37].…”
Section: Decision Of Prophylactic Cholecystectomy In the Real Worldmentioning
confidence: 95%
“…The HR for all-cause mortality among the cholecystectomy cohort was 0.75 (95% CI = 0.59-0.95; p = 0.016) compared with the control cohort. The authors concluded that prophylactic cholecystectomy should be recommended in these elderly patients [36]. Furthermore, in a population-based study of patients over 65 years of age, prophylactic cholecystectomy was significantly associated with a 50-70% RR reduction in recurrent CBD stones, cholangitis, and gallstone pancreatitis compared to only ES.…”
Section: Patients With Gb Stonesmentioning
confidence: 98%
“…Following Cotton's pioneering description of cannulation of the common bile duct (CBD) and McCune's first successful ERCP in the mid-1970's, ERCP has been widely adopted as the index therapeutic modality for clearance of CBD stones [4][5][6] and is most commonly performed either prior to or after operative removal of the gallstone reservoir at laparoscopic cholecystectomy. There have been variable approaches to sphincterotomy during ERCP with some preferring balloon dilation and others sphincterotomy [7][8][9]. Increasingly, ERCP is performed intra-operatively with a rendezvous technique with favourable outcomes reported [10][11][12].…”
Section: Introductionmentioning
confidence: 99%